The makeover reality television and reflexive audiences - Sender, Katherine (Critical cultural communication., 2012)
Watch this show, buy this product, you can be a whole new you! Makeover television shows repeatedly promise self-renewal and the opportunity for reinvention, but what do we know about the people who watch them? As it turns out, surprisingly little. The Makeover is the first book to consider the rapid rise of makeover shows from the perspectives of their viewers. Katherine Sender argues that this genre of reality television continues a long history of self-improvement, shaped through contemporary media, technological, and economic contexts. Most people think that reality television viewers.